Daijokito Administration in Critically Ill Patients Increasing the Stool Volume: A Retrospective Observational Study - Satoh, Kasumi; Nakae, Hajime (Frontiers in Nutrition, 2021)
Introduction:Daijokito, a traditional Japanese herbal medicine (Kampo), has been used to treat abdominal distention of the middle yang stage pattern. The use of Daijokito has not been thoroughly investigated in critical care. To investigate a new Kampo approach to defecation control in critically ill patients, our study aimed to assess the effects of Daijokito on fecal management. Methods: We analyzed 30 consecutive patients treated with Daijokito in the intensive care unit (ICU) between March 2017 and February 2021. The eligibility criteria were patients who were newly prescribed Daijokito in the ICU during the study period. Exclusion criteria were patients who were started on other laxatives within one day of beginning Daijokito. The study's primary outcome was defecation volume three days before and three days after starting Daijokito. We recorded the most dominant stool quality within three days after the start of Daijokito. Results: Twenty-one patients were included in the analysis. The median age was 69.0 years, and the median sequential organ failure assessment score on admission to the ICU was 6.0. Major diseases included trauma, pancreatitis, and burns. Administration of Daijokito resulted in defecation in 17 of twenty-one patients (81.0%). Comparison of defecation volume between 3 days before Daijokito administration and three days, including the day of Daijokito administration, showed that defecation volume increased significantly after Daijokito administration, with a median of 0 to 360 g (p < 0.001). At the three-day follow-up, six of 17 (35.3%) patients defecated on the day of Daijokito administration, and nine (52.9%) defecated on the day after administration. One patient was judged to have excessive defecation, and Daijokito administration was discontinued. Stool quality was normal in one (5.9%) of the 17 patients, soft-formed in two (11.8%), loose-unformed in 11 (64.7%), and liquid in three (17.6%). Discussion:Daijokito administration in critically ill patients caused defecation in 81% of the patients and significantly increased stool volume. The novelty of this study is that it sheds light on the Kampo treatment of defecation control in critically ill patients. In addition to the present report, further studies are warranted to quantify the therapeutic efficacy and safety of Daijokito.